(3cJGH aj GdML hefGScgs
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeg hjcGaF eRjOg CeG HYO abO SCdfi LeGYI aCLHJ SDGdge , hCbJUQJ Ydi GdCge , hde CPcQ cKjQkG ef GdaQhY hQJHJg Ydi SHYI CHhGH (B: (3GdHGH GdChd (B: (3ai aVd GdML GdKGfi (B: (3ai GdEMQGe s
(3BNQgG (B:s
(3BNQ G dehLhO efgG (B: (3GdHGH GdSGHY hjVYa bhd GdRLGL Ef HfGA HjJ GdebOS ef HfGA SdjeGf Ydjg GdSdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3YdjgG hba HGSe SjO YHO GdQMef GdeShe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3CUhd Gdabgs